Revitalisasi Makna dan Estetika Batik Parang: Dari Sakralitas Keraton ke Ekspresi Kontemporer - Pandanwangi, Ariesa; Ernawan, Erika; Suryana, Wawan; Effendi, Ismet Zainal (Jayapangus Press, 2025)
Parang batik is a very important form of cultural heritage, possessing sacred value. This batik originated from the palace environment and was worn by a limited circle. The challenge arose regarding how to revitalize the Parang motif so that it could be accepted and worn by the younger generation without losing its philosophical value. The goal was to introduce new values to the Parang batik motif, with the hope that it could be integrated into the creative industry in the future. A qualitative descriptive method with a historical approach was used to uncover the origins of the Parang batik motif and its philosophical meaning. An artistic approach was then used to reveal the results of the revitalization, which were analyzed through visual objects. The composition, pattern structure, and color were analyzed to reveal the results of the revitalization. This process involved adjusting the visual form while maintaining the motif's identity. However, aesthetic touches were added that were in line with the tastes of the younger generation. The results obtained include samples of Parang batik from the revitalization process. The background of the Parang motif was retained, but additional visual elements in the form of horizontal floral arrangements were added at the bottom of the fabric, creating a more modern compositional dynamic. The floral pattern is repeated vertically in bold colors, which differs from the traditional, more muted colors. This study concludes that the revitalization of Parang batik was achieved by using striking colors while maintaining the background of the Parang motif.